Galectin-9 inhibits cell proliferation and induces apoptosis in Jurkat and KE-37 acute lymphoblastic leukemia cell lines via caspase-3 activation - Narges Zargar Balajam; Mahdi Shabani; Mahmoud Aghaei (Research in Pharmaceutical Sciences, 2021)
Background and purpose: Acute lymphoblastic leukemia (ALL) is a type of cancer of blood and bone marrow characterized by abnormal proliferation of lymphoid progenitor cells. Galectin-9 is a tandem-repeat type galectin expressed in various tumor cells. It seems that the connection between galectin-9 and T cell immunoglobulin mucin-3 receptor acts as a negative regulator of cancer cells proliferation. Experimental approach: In this research, the effects of galectin-9 were investigated using MTS cell proliferation colorimetric, colony-forming, annexin V-FITC/PI, and caspase-3 assays in the Jurkat and KE-37 cell lines of ALL. Furthermore, the western blotting technique was used to evaluate the levels of apoptotic proteins such as Bax and Bcl-2 in these cell lines. Findings/Results: Our results indicated that galectin-9 can considerably reduce the cell growth and colony formation ability of both Jurkat and KE-37 cell lines in a concentration-dependent manner. Besides, galectin-9 induced apoptosis in a concentration-dependent manner in ALL cells by a mechanism associated with Bax/Bcl-2 expression and activation of the caspase-3 activation. Conclusion and implications: Galectin-9 inhibited the growth and proliferation of cell lines with increased programmed cell death, therefore it can be considered as a potential factor in the progression of ALL therapeutics that needs more research in this context.